Effects of anti-neutrophil cytoplasm autoantibodies on tissue factor activity by HL-60 cells in vitro - Flores-Suárez, Luis Felipe; Nowack, Rainer; Yard, Benito A.; Dempfle, Carl-Erik; Woude, Fokko J. van der (Scandinavian journal of immunology, 2003)
The effects of cytoplasmic anti-neutrophil cytoplasm autoantibodies (C-ANCA) and perinuclear ANCA (P-ANCA) immunoglobulin G (IgG) on tissue factor (TF) activity using HL-60 cells in vitro were compared with those of medium, lipopolysaccharide (LPS) and control IgG. Cells were also incubated with both ANCA IgG and control IgG in the presence of a submaximal concentration of LPS capable of upregulating TF procoagulant activity (TF-PCA) measured in arbitrary units of TF equivalent (AU-TFEq). The purpose was to search for an additive effect between LPS and ANCA IgG. All IgG preparations increased HL-60 cell TF-PCA in comparison with the medium. When cells were incubated with P-ANCA IgG and LPS (1 micro g/ml), a larger increase was seen (151.23 +/- 31.6 SEM (standard error of the mean) AU-TFEq) than when incubated with control IgG plus LPS (91.01 +/- 18.4 SEM AU-TFEq; P < 0.005), P-ANCA IgG alone (73.68 +/- 12.7 SEM AU-TFEq; P < 0.005) or LPS (1 micro g/ml) (58.11 +/- 7.9 SEM AU-TFEq; P < 0.005). There was concordance between PCA and TF total antigen content by enzyme-linked immunosorbent assay (ELISA). The fact that P-ANCA IgGs upregulate the function of TF in HL-60 cells in combination with LPS adds to information regarding the possible role of ANCAs in the enhancement of TF by different cells, although it does not support the fact that ANCAs alone play a role in mononuclear cell TF upregulation. The additive effects of LPS underline the possible role of pro-inflammatory stimuli in the pathogenesis of ANCA-associated diseases.
First published: 28 January 2003
Gesehen am 15.06.2022